Nonlinear dynamical analysis of interaction between a three-dimensional rubberlike membrane and liquid in a rectangular tank - Parasil, Worawat; Watanabe, Naoyuki (International Journal of Non-Linear Mechanics, 2016)
Membrane–liquid interactions occur in many areas of engineering and it is important to understand their properties. To overcome the difficulties caused by the presence of a moving boundary due to large deformations, an arbitrary Lagrangian–Eulerian (ALE) description is used. An analytical model of membrane–liquid interaction in a rectangular tank is investigated and an analytical technique that can be adapted to domains subject to large deformations is developed. A number of parametric calculations are performed, and some nonlinear characteristics are obtained that confirm the validity of the approach presented here. •The nonlinear characteristics of membrane and liquid were examined.•An ALE description was used to solve the large deformation problems.•The validity of the analysis in the large-deformation domain thus confirmed.•The nonlinearities are strong at a large excitation.